(untitled) (American Journal of Technology and Applied Sciences, 2023)
This article analyzes the genesis of riddles, features of the genre. The types of riddles in Uzbek and Turkish folklore are compared, and their common and different aspects are determined. The analysis is supported by examples from riddles of both nations.